Neo-liberalism, social democracy or a social market system in South Africa? : A Christian-ethical appraisal - Vorster, JM (Stellenbosch Theological Journal, 2020)
Despite the establishment of a full democracy in South Africa 25 years ago, the economy of the country has not answered to the ideals of economic growth and the alleviation of poverty as set by the various parties at the dawn of this new dispensation. Several political administrations have since endeavoured to address the problem with different plans and economic programmes. Characteristic of these plans is the fact that the focus fluctuated between neo-liberal principles and government-regulated social democratic ideas. The programmes reflect the vigorous debate in South African political circles between proponents of the neo-liberal philosophy of the economy and proponents of social democracy. The debated question is: What economic policy will suit South Africa to enable this country to deal with the perennial poverty and inequality in the best way? Should it be mere neo-liberalism or an authoritarian social democratic philosophy? This article aims to introduce a Christian-ethical perspective on the qualities of South African versions of neo-liberalism and socio-democracy in view of the obligation of the markets and the government to pursue the best policy to alleviate poverty and its various social effects. The central theoretical argument of this article is that a Christian-ethical approach holds that the government of the day is responsible to address poverty by applying a policy of economic growth that is immediately effective and sustainable on the long run. This policy entails a strategy that can be termed a "social market economy", which sustains the freedom of the market, but facilitates limited government involvement in the economy on behalf of the poor.